FLOW TESTING TOOL FOR STUDENTS’ SOFTWARE PROJECT - ISAM MUDDIN, NURUL AINUL AFIQAH (IRC, 2020)
Every Information Technology (IT) and Information System (IS) students of Universiti Teknologi PETRONAS (UTP) must have experienced handling of some software projects for their courses throughout their study years. The students, especially those in their earlier years of study, may face challenging moments in carrying out those projects especially when it comes to the software testing phases. Often time, with limited experience in software development, the students might not even know how to carry out proper flow test. Hence, this project intends to propose the development of a software flow testing tool to assist students in performing flow test on their software projects focusing on the black box testing. Black box testing is one of the software testing approaches which not depending on the software codes, which can be completed by using the system requirements. Students can implement this testing approaches at the early stage of the system development and at the end of the project development. With the tool, the flow testing will be more guided and follow approaches which exists in the software engineering domain. This project started off with some preliminary studies, surveys, and literature review on existing software engineering approaches for software testing. Furthermore, Rapid Application Development (RAD) approach has been selected as methodology for the Software Development Life Cycle (SDLC) of the tool. Results from initial works have supported the need for the tool, as well as feasibility for such tool to be developed.